2016
DOI: 10.3892/ol.2016.4913
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume provides beneficial diagnostic and prognostic information for patients with resectable gastric cancer

Abstract: Gastric cancer is the fourth most frequent cancer and the second cause of cancer-related mortalities worldwide. Platelets play an important and multifaceted role in cancer progression. Elevated mean platelet volume (MPV) detected in peripheral blood has been identified in various types of cancer. In the present study, we investigated the application value of MPV in early diagnostic and prognostic prediction in patients with resectable gastric cancer. In total, 168 patients with resectable gastric cancer were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 22 publications
3
52
2
Order By: Relevance
“…On the other hand, as the estrogen concentration increases, the anti‐inflammatory pathway becomes active . To date, the relationship between many types of cancer and MPV has been investigated . All authors reported that MPV could be used as a cheap, non‐invasive marker for cancer diagnosis and prognosis in these publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, as the estrogen concentration increases, the anti‐inflammatory pathway becomes active . To date, the relationship between many types of cancer and MPV has been investigated . All authors reported that MPV could be used as a cheap, non‐invasive marker for cancer diagnosis and prognosis in these publications.…”
Section: Discussionmentioning
confidence: 99%
“…7 To date, the relationship between many types of cancer and MPV has been investigated. [20][21][22][23][24][25][26] All authors reported that MPV could be used as a cheap, non-invasive…”
Section: B-cell Activation Is a Harmful Factor In B Cell-mediated Dismentioning
confidence: 99%
“…The research performed by Shen XM. et al in a case-control study on 168 patients with resectable gastric cancer showed that the pre-operatic mean platelet volume (MPV) was significantly higher in patients with gastric cancer compared with the healthy control group and a low pre-operatic MPV level and antiplatelet therapy independently related to better histopathological features and improved overall survival in gastric cancer patients (19). On the one hand, there is a concordance of our findings regarding that NSAIDs and antiplatelet therapy was not associated with the occurrence of inflammatory or premalignant gastric lesions (p>0.05) and the data described in the literature which demonstrate that regular use of non-selective NSAIDs, including aspirin, is an effective chemopreventive strategy for the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mean platelet volume (MPV), the most commonly used index of platelet size, is a surrogate marker of platelet activation 10 . Altered MPV levels were observed in gastric cancer, ovarian cancer, lung cancer, colon cancer, and breast cancer 11 14 . However, its clinical implications in RCC have not been reported.…”
Section: Introductionmentioning
confidence: 99%